Environmental and Medical Aspects of the Glauconite Application - Nikolaevskiy, V.A.; Tanygina, E.D. (Journal of Applied Solution Chemistry and Modeling, 2022)
The possibility of the effectiveness of increasing the wound healing, increasing the strength of the scar, and reducing the signs of the wound inflammation when replacing Panthenolspray (AEROPHARM, Germany) with glauconite powder has been investigated during the process of the experimental research. Glauconite powder can be used in the treatment of infected wounds and burns.